Multilevel Categoric-One Factor Optimization Of Cremophor Rh 40 As Surfactant in Cream With Calabash (Crescentia cujete Linn) Leaves Ethanolic Extract - Winanti Adi Riyanti; Dewi Wulandari Auliasari; Kharisma Raudlatul Firdaus; Malinda Prihantini (Universitas Wahid Hasyim Semarang, 2024)
Indonesia's location on the equator is exposed to a high UV index, which triggers various health problems due to ultraviolet radiation, including melanoma. Melanoma is the 5th deadliest cancer that develops from the malignant transformation of melanin in oxidative stress conditions. Therefore, antioxidants are needed. Calabash is a natural exogenous antioxidant with an IC₅₀ value of 80.21 µg/mL (strong activity). Optimal formulations of cream containing calabash are determined by the concentration of ingredients and the selection of comprehensive analytical methods. This research aims to optimize cream preparations of calabash leaves ethanol extract with varying concentrations of Cremophor RH 40 as a surfactant using the multilevel categoric-one factor method. The cream was made with Cremophor RH 40 concentrations of 5%, 10%, and 15%. The cream was made by mixing the water phase (Nipagin, Glycerine, and Aquadest) and the oil phase (Cremophor RH 40, BHT, IPM, Cetostearyl alcohol, and Nipasol) after both phases reached a temperature of 60ºC in mixer speed no 1 for 15 minutes then followed by adding calabash leaves ethanolic extract until a homogeneous cream was formed. The parameters observed were organoleptic, homogeneity, the type of cream, pH, viscosity, dispersibility, and adhesion. The viscosity, dispersibility, and adhesion were chosen as the parameters for the formula optimization. The cream of calabash ethanolic extract was shown as green, homogeneous semi-solid with a soft texture and distinctive aroma, and was an oil-in-water (O/W) type cream. The average pH of 5.6 was suitable for facial skin. The viscosity value increased with increasing surfactant concentration while dispersibility decreased. The results of formula optimization obtained the optimum formula was FIII with a concentration of Cremophor RH 40 of 15% and a desirability value of 0,896.